2002
DOI: 10.1002/1521-3919(20020601)11:5<587::aid-mats587>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Structural Organization of Water-Containing Nafion: A Cellular-Automaton-Based Simulation

Abstract: Using the cellular‐automaton‐based simulation technique, we study the processes of self‐organization in the systems of comb‐like copolymers with strongly attracting (end‐functionalized) side‐chains in the presence of low‐molecular‐weight water‐like solvent. This molecular level modeling reflects the basic features of the specific structural organization of perfluorosulfonic acid ionomer (Nafion) with certain amount of physisorbed water. We compare the simulation data with the existing phenomenological models u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 32 publications
(108 reference statements)
2
43
1
Order By: Relevance
“…Since this is much higher than the water content required experimentally for conductivity, it was concluded that there may be proton transport through waterdepleted regions either by interfacial diffusion in close promixity to sulfonate groups or through a second ionic phase with smaller channels than those resolvable using mesoscopic simulations. Similarly to the work of Mologin et al 85 described above, these results cast doubt on the utility of the concept of percolation as a direct requirement for the onset of conductivity. The authors conclude that the structures responsible for the low ''percolation'' thresholds for conductivity in PFSA membranes remain elusive, and propose that these be investigated further by multiscale simulations involving both explicit molecular calculations as well as a mesoscale component.…”
Section: Mesoscale Modelsmentioning
confidence: 72%
See 1 more Smart Citation
“…Since this is much higher than the water content required experimentally for conductivity, it was concluded that there may be proton transport through waterdepleted regions either by interfacial diffusion in close promixity to sulfonate groups or through a second ionic phase with smaller channels than those resolvable using mesoscopic simulations. Similarly to the work of Mologin et al 85 described above, these results cast doubt on the utility of the concept of percolation as a direct requirement for the onset of conductivity. The authors conclude that the structures responsible for the low ''percolation'' thresholds for conductivity in PFSA membranes remain elusive, and propose that these be investigated further by multiscale simulations involving both explicit molecular calculations as well as a mesoscale component.…”
Section: Mesoscale Modelsmentioning
confidence: 72%
“…In a later study using coarse-grained methods, Mologin et al 85 described a lattice molecular dynamics (LMD) approach, which they referred to as a ''cellular automaton'' simulation method, based on a coarse-grained model for the polymer chains with variable bond lengths between connected nodes, similar to a bond fluctuation model (BFM), 86 but with deterministic rules for propagation of polymer segments on the lattice as opposed to stochastic evolution in the standard MC approach. According to Khoklov et al, 87,88 the LMD approach is capable of yielding convergence to limiting distribution functions nearly an order of magnitude faster than typical MC lattice-based simulations of polymers.…”
Section: Mesoscale Modelsmentioning
confidence: 99%
“…It is well known that the proton conductivity of hydrated Nafion membranes starts to increase considerably already at very low water content [3,[12][13][14][29][30][31]. This fact suggests that the ionic conductive channels can exist in the microphase-separated structure of nearly dry membranes [12].…”
Section: Resultsmentioning
confidence: 99%
“…[46][47][48][49] Because of computational limitations, full atomistic models are not able to probe the random morphology of these systems. However, as demonstrated by these simulations and applications to other random composite media, mesoscale models are computationally feasible to capture the morphology.…”
Section: F60mentioning
confidence: 99%